Special pedagogy at a crossroads. Perspectives of contemporary special pedagogy - DRYŻAŁOWSKA, GRAŻYNA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2019)
Grażyna Dryżałowska, Special pedagogy at a crossroads. Perspectives of contemporary special pedagogy. Interdisciplinary Contexts of Special Pedagogy, no. 25, Poznań 2019. Pp. 105-125. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2019.25.05 The article is an attempt to reflect on the difficult situation in which special pedagogy was found. It is more difficult than the crisis that took place after 1989, because the fascination with the idea of normalisation and integration is gradually decreasing, and there is no new concepts for the further development of special education as a scientific sub-discipline obliged to respond to modern challenges.